MRI brain volume loss, lesion burden, and clinical outcome in secondary progressive multiple sclerosis. (April 2022) - Koch, Marcus W; Mostert, Jop; Repovic, Pavle; Bowen, James D; Strijbis, Eva; Uitdehaag, Bernard; Cutter, Gary
Background: Magnetic resonance imaging (MRI) of brain volume measures are widely used outcomes in secondary progressive multiple sclerosis (SPMS), but it is unclear whether they are associated with physical and cognitive disability. Objective: To investigate the association between MRI outcomes and physical and cognitive disability worsening in people with SPMS. Methods: We used data from ASCEND, a large randomized controlled trial ( n = 889). We investigated the association of change in whole brain and gray matter volume, contrast enhancing lesions, and T2 lesions with significant worsening on the Expanded Disability Status Scale (EDSS), Timed 25-Foot Walk (T25FW), Nine-Hole Peg Test (NHPT), and Symbol Digit Modalities Test (SDMT) with logistic regression models. Results: We found no association between MRI measures and EDSS or SDMT worsening. T25FW worsening at 48 and 96 weeks, and NHPT worsening at 96 weeks were associated with cumulative new or newly enlarging T2 lesions at 96 weeks. NHPT worsening at 48 and 96 weeks was associated with normalized brain volume loss at 48 weeks, but not with other MRI outcomes. Conclusion: The association of standard MRI outcomes and disability was noticeably weak and inconsistent over 2 years of follow-up. These MRI outcomes may not be useful surrogates of disability measures in SPMS.